Stimulasi Keterampilan Proses Sains Anak Melalui Model Pembelajaran Sains Berbasis Proyek - Niken Farida (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2021)
This study aims to improve the science process skills of children aged 5-6 years through a project-based learning model. This research is a type of quasy experiment with an equivalent time series design. The research subjects consisted of 88 group children, namely children aged 5-6 years from 6 Kindergartens in Sleman Regency. Data collection was carried out using observation. Then the data were analyzed using one way ANOVA and got the sig value. 0.00, which means that there is a difference in the mean ranking of process science skills after using a project-based science learning model, so the results of this study indicate that an effective project-based science learning model is used to improve science process skills of children aged 5-6 years.